Quantum‐chemistry descriptors for photosensitizers based on macrocycles. (February 2017) - Bettanin, Fernanda; Antonio, Felipe C. T.; Honorio, Kathia M.; Homem‐de‐Mello, Paula
Abstract : Phthalocyanines, porphyrins, and chlorins have been widely studied as photosensitizers. Both experimental and computational strategies are employed in order to propose new and more active molecules derived from those macrocycles. In this context, there are two main strategies used: (i) the addition of different substituents and (ii) the complexation of the macrocycle with different metallic ions. In this work, we present selected descriptors based on quantum chemistry calculations for forty macrocycles, including some approved drugs. We have found that density functional theory is a suitable methodology to study the large sets of molecules when applying the B3LYP/LanL2DZ methodology for geometry optimization and TD‐OLYP/6‐31G(d) for absorption spectrum. The inclusion of solvent effects by means of continuum model is important in order to obtain the accurate electronic data. We have verified that by bonding charged or polar substituents to the macrocycle, it is possible to enhance water solvation as well as to improve spectroscopic properties because molecular orbital contributions for Q band can be affected by some substituents. Selected descriptors, electronic and steric, were pointed out as important to propose the new photosensitizers. Abstract : We have found an approach based on density functional theory and continuum model to study a large set of macrocycle molecules. The bonding of charged or polar substituents to the macrocycle enhances the macrocycle solvation and improves spectroscopic properties. We have also selected steric and electronic descriptors in order to propose new photosensitizers.